The irony of Spain’s imperial denouement : afrancesamiento in Leopoldo Alas Clarin’s La Regenta (1884) - Cuzovic-Severn, Marina (2020)
Fil: Cuzovic-Severn, Marina. Universidad Estatal de California; Estados Unidos